{-# OPTIONS --without-K --safe #-}
module Equality.Propositional where
open import Equality
open import Logical-equivalence hiding (_∘_)
open import Prelude
open import Agda.Builtin.Equality public using (_≡_; refl)
private
refl′ : ∀ {a} {A : Set a} (x : A) → x ≡ x
refl′ x = refl
elim : ∀ {a p} {A : Set a} {x y}
(P : {x y : A} → x ≡ y → Set p) →
(∀ x → P (refl′ x)) →
(x≡y : x ≡ y) → P x≡y
elim P r refl = r _
elim-refl : ∀ {a p} {A : Set a} {x}
(P : {x y : A} → x ≡ y → Set p)
(r : ∀ x → P (refl′ x)) →
elim P r (refl′ x) ≡ r x
elim-refl P r = refl
reflexive-relation : ∀ ℓ → Reflexive-relation ℓ
Reflexive-relation._≡_ (reflexive-relation _) = _≡_
Reflexive-relation.refl (reflexive-relation _) = refl′
equality-with-J₀ : ∀ {a p} → Equality-with-J₀ a p reflexive-relation
Equality-with-J₀.elim equality-with-J₀ = elim
Equality-with-J₀.elim-refl equality-with-J₀ = elim-refl
equivalence-relation⁺ : ∀ ℓ → Equivalence-relation⁺ ℓ
equivalence-relation⁺ _ = J₀⇒Equivalence-relation⁺ equality-with-J₀
equality-with-J : ∀ {a p} → Equality-with-J a p equivalence-relation⁺
equality-with-J .Equality-with-J.equality-with-J₀ = J₀⇒J equality-with-J₀ .Equality-with-J.equality-with-J₀
equality-with-J .Equality-with-J.cong = J₀⇒J equality-with-J₀ .Equality-with-J.cong
equality-with-J .Equality-with-J.cong-refl = J₀⇒J equality-with-J₀ .Equality-with-J.cong-refl
equality-with-J .Equality-with-J.subst = J₀⇒J equality-with-J₀ .Equality-with-J.subst
equality-with-J .Equality-with-J.subst-refl = J₀⇒J equality-with-J₀ .Equality-with-J.subst-refl
equality-with-J .Equality-with-J.dcong = J₀⇒J equality-with-J₀ .Equality-with-J.dcong
equality-with-J .Equality-with-J.dcong-refl = J₀⇒J equality-with-J₀ .Equality-with-J.dcong-refl
open Derived-definitions-and-properties equality-with-J public
hiding (_≡_; refl; reflexive-relation; equality-with-J₀)